2005
DOI: 10.1007/s00432-005-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

The tobacco-specific carcinogen, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone stimulates proliferation of immortalized human pancreatic duct epithelia through β-adrenergic transactivation of EGF receptors

Abstract: These findings suggest that the NNK -mediated beta-adrenergic receptor transactivation of the EGFR and phosphorylation of Erk1/2 in immortalized human pancreatic duct epithelial cells as a novel mechanism might contribute to the development of tobacco-associated pancreatic carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
105
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 30 publications
9
105
1
2
Order By: Relevance
“…β-AR agonists and EGF increase EGFR phosphorylation EGFR transactivation was caused by binding of β-AR agonist to its receptor [5] . Both cells were treated with β-AR ligands alone or in combinations for 10 min.…”
Section: β-Ar Agonists and Forskolin Increase Camp Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…β-AR agonists and EGF increase EGFR phosphorylation EGFR transactivation was caused by binding of β-AR agonist to its receptor [5] . Both cells were treated with β-AR ligands alone or in combinations for 10 min.…”
Section: β-Ar Agonists and Forskolin Increase Camp Accumulationmentioning
confidence: 99%
“…A normal pancreatic duct epithelial cell line and several pancreatic cancer cell lines express β1 and/or β2-ARs as well as epidermal growth factor receptor (EGFR) including Panc-1, BXPC-3, PC-2, PC-3, and HPDE6-c7. Moreover, the EGFR is frequently over-expressed in pancreatic cancer [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…However, in these cells, carcinogenic events are unlikely to be mediated by a disturbance of the physiologic regulation. In vitro, the impact of polycyclic aromatic hydrocarbons and NNK, two cigarette smoke-associated carcinogens, was investigated in immortalized pancreatic ductal cells [61][62]. In these studies, NNK increased the proliferation of pancreatic ductal cells by beta-adrenergic receptor transactivation of EGFR with downstream ERK 1/2 phosphorylation, indicating one potential pro-carcinogenic effect of NNK [61].…”
Section: Inflammation Alters Regulation Of Ductal Genesmentioning
confidence: 99%
“…35 A recent study reported NNK, the tobacco-specific carcinogen, stimulates proliferation of HPDE6-c7 cells. 36 To determine a potential mechanistic effect of cigarette smoke on biologically relevant cell type, we determined specific structure-activity effects of methylanthracene isomers, which are some of the most prevalent polycyclic aromatic hydrocarbons found in cigarette smoke condensates, 37 on GJIC and stem cell markers in the pluripotent pancreatic stem cell line (HPDE6-E6E7c7).…”
mentioning
confidence: 99%